Layer-Based ID Assigning Method for Sensor Networks - Kang, Jung Hun; Park, Myong-Soon (Ubiquitous Convergence Technology, 2007)
A sensor network consists of a set of battery-powered nodes, which collaborate to perform sensing tasks in a given environment. Globally unique ID allocation is usually not applicable in a sensor network due to the massive production of cheap sensor nodes, the limited bandwidth, and the size of the payload. However, locally unique IDs are still necessary for nodes to implement communications to save energy consumption. Already several solutions have been proposed for supporting locally unique ID assignment in sensor networks. However, they bring much communication overhead, and they are complex to implement. We present a layer-based algorithm to solve the unique ID assignment problem. This algorithm can save energy consumption by reducing communication overhead while IDs are assigned.